ANALISIS KETIDAKSEIMBANGAN ARUS DI PLTDG PESANGGARAN - Mawahib Mahmud; I Wayan Sutama (Universitas Pendidikan Nasional, 2019)
The Electricity System in Bali continues to experience growth every year, where increasing demand for electricity is affected by the increase in the number of electricity consumers in one phase and consumers of electricity in three phases. The Gas Diesel Power Plant (PLTDG) in fulfilling the electricity needs in Bali can supply 200 MW of electricity, sourced from 12 generators. Along with the increase in various types of electricity consumers in Bali, the problem arises in the PLTDG Pesanggaran, namely the occurrence of unbalanced current. A large unbalanced current can cause a trip or a sudden death at the PLTDG Pesanggaran’s generator.Based on the results of the study, the percentage of unbalanced current that occur in the PLTDG in normal conditions ranges between 2% to 3%. But at the time of the trip to the unit 6 generator due to unbalanced current, the percentage of unbalanced current that appeared on the generator just before the trip was 21.69% and has been going on for more than 58 minutes, which exceeds the setting of the relay which only allows a percentage unbalanced current under 8% with a maximum time of 58 minutes. During the trip, the generator only operated 1 unit in block 2, so the magnitude of the unbalanced carried by the generator unit 6 itself.